Maternal Trichomonas vaginalis as a risk factor of spontaneous preterm labour in Southwest Nigeria: a case-control study - Adetokunbo Agbolade Oyeleye; Muisi Alli Adenekan; Akeem Abayomi Agbetoba; Emeka Chinedum Nkwo; Sunday Isaac Omisakin; Kayode Ayodeji Adefemi; Aloy Okechukwu Ugwu (Universa Medicina, 2026)
BackgroundTrichomonas vaginalis is a sexually transmitted protozoan infection associated with adverse pregnancy outcomes, including spontaneous preterm labour. The proposed mechanism involves genital tract inflammation, which may trigger cervical changes and uterine contractions. This study assessed whether T. vaginalis infection was associated with spontaneous preterm labour among pregnant women at Lagos Island Maternity Hospital, Lagos, Nigeria. MethodsThis case-control study recruited 520 pregnant women, comprising 260 women with spontaneous preterm labour and 260 women who delivered at term. Vaginal swabs were collected using sterile swab sticks.  Wet mount microscopy and culture were performed to detect T. vaginalis. The association between T. vaginalis infection and spontaneous preterm labour was assessed using the Chi-square test, while binary logistic regression was used to adjust for potential confounders. Statistical significance was set at p<0.05. ResultsThe mean age of participants was comparable between the preterm and term labour groups: 30.1 ± 5.3 years versus 29.8 ± 6.2 years, respectively (p=0.625). T. vaginalis infection was more prevalent among women with spontaneous preterm labour than controls, 16.9% versus 10.2%. On unadjusted analysis, infection was significantly associated with spontaneous preterm labour (OR 1.78, p=0.028). However, after adjustment for confounders, the association was no longer statistically significant (aOR 1.34, 95% CI 0.72–2.51, p=0.351). ConclusionT. vaginalis infection was more common among women with spontaneous preterm labour, but the association was not independently significant after adjustment. Comprehensive antenatal risk assessment remains essential.